Reaching sustainable food security for all by 2020: getting the priorities and responsibilities right - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
As part of its 2020 Vision for Food, Agriculture, and the Environment Initiative, the International Food Policy Research Institute (IFPRI) has articulated a vision of what the world should look like in 2020: it should be a world free from poverty, hunger, malnutrition, and unsustainable natural resource management. The 2020 Vision Initiative has two main objectives: (1) to develop and promote a shared vision and consensus for action for meeting food needs while reducing poverty and protecting the environment; and (2) to generate information and encourage debate to influence action by national governments, nongovernmental organizations, business and industry, international development institutions, farmers, and other elements of civil society. In September 2001, IFPRI and its 2020 Vision Initiative, in collaboration with partners, sponsored an international conference in Bonn, Germany, to bring together the actors needed to achieve this vision. The 900 people who attended the conference considered the driving forces that will determine the difficulty of achieving the 2020 Vision, and they articulated the steps required to build the world the Vision describes.This document reflects many of their discussions. Compiled here is what is known about the conditions facing the world in the next 20 years and about how to overcome the persistent and interlocking problems of food insecurity, poverty, and environmental degradation. -- Introduction.